Penerapan teknologi hidroponik sistem deep flow technique sebagai usaha peningkatan pendapatan petani di Desa Sungai Bawang - Fitmawati Fitmawati; Isnaini Isnaini; Siti Fatonah; Nery Sofiyanti; Rodesia Mustika Roza (Riau Journal of Empowerment, 2018)
The target becomes a self-reliant village must be accompanied by strengthening village ability in supplying the basic needs independently. Vegetables are one of the crucial basic needs to achieve a healthy and prosperous society. The demand for vegetables in Sungai Bawang Village, Kuantan Singingi Regency, is constrained by the available land for vegetable farming. Hydroponic planting system offers the technique without soil that can be implemented anywhere. It has added value in providing clean and hygienic vegetables. Hydroponics technology system of Deep Flow Technique able to provide water and oxygen for plants and suitable for leafy vegetables. Hydroponic is appropriate to be implemented in Sungai Bawang village and did not require huge land in applying this technology. The mentoring strategy is carried out by counseling and demonstration of direct planting stages and the practice by the community. This activity gave a positive influence on the community as well as many people who want to apply this technology. This was the first step in increasing the income of the community, especially farmers. And for the community in general, this technology facilitates the people to get vegetables easily at an affordable price.